2011
DOI: 10.1007/s11524-011-9580-7
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Injuries in the Slums of Nairobi and their Risk Factors: Results from a Matched Case-Control Study

Abstract: Injuries contribute significantly to the rising morbidity and mortality attributable to non-communicable diseases in the developing world. Unfortunately, active injury surveillance is lacking in many developing countries, including Kenya. This study aims to describe and identify causes of and risk factors for fatal injuries in two slums in Nairobi city using a demographic surveillance system framework. The causes of death are determined using verbal autopsies. We used a nested case-control study design with al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 22 publications
1
34
2
Order By: Relevance
“…We found that alcohol drinking behavior, previous gender based violence, consumption of homemade illicit brew and/or use of drug such as cannabis were surprisingly risk factors for homicide victimization in Rwanda post genocide regardless of gender status of homicide victims. Our results were consistent with findings of other studies, conducted in Tanzania and Kenya, two neighboring East African countries with relatively similar socio-economic situations [ 5 , 17 ]. However, these risk factors are not specific to sub-Saharan African countries, as evidenced by the findings on homicide risk factors in Sweden and United States [ 1 , 2 ].…”
Section: Discussionsupporting
confidence: 93%
“…We found that alcohol drinking behavior, previous gender based violence, consumption of homemade illicit brew and/or use of drug such as cannabis were surprisingly risk factors for homicide victimization in Rwanda post genocide regardless of gender status of homicide victims. Our results were consistent with findings of other studies, conducted in Tanzania and Kenya, two neighboring East African countries with relatively similar socio-economic situations [ 5 , 17 ]. However, these risk factors are not specific to sub-Saharan African countries, as evidenced by the findings on homicide risk factors in Sweden and United States [ 1 , 2 ].…”
Section: Discussionsupporting
confidence: 93%
“…Deaths from firearm discharge (23 %) and road traffic accidents (22 %) were the leading single causes of deaths due to injuries. 54 Globally, young men are particularly vulnerable to deaths from injuries than women due to a number of reasons including but not limited to higher risk taking tendencies-overspeeding when driving, alcohol and illicit substance abuse, and higher proneness to commit violent crime.…”
Section: Discussionmentioning
confidence: 99%
“…Between 60 and 70 percent of the city's residents are estimated to live in slums or slumlike conditions 4,6,14 . Slum-dwellers also have limited access to health and reproductive health services, have higher morbidity and mortality, and are more likely to engage in risky sexual behaviors 15,16,[15][16][17][18][19][20][21][22][23][24]14,25,26,27 . In particular, slum residents are known to have poorer sexual and reproductive health outcomes than their counterparts living in other parts of the city or in rural areas 28 .…”
mentioning
confidence: 99%